Pengaruh Terapi Musik Gamelan Terhadap Kulitas Tidur Lansia di Desa Bateran kecamatan Sumbang 2021 - Nanik Yuniarti; Prasanti Adriani; Suci Khasanah (CV. ALIM'SPUBLISHING, 2024)
A person's happiness with their sleep and the absence of symptoms of sleep deprivation and difficulty sleeping are indicators of good sleep quality. Sleep quality includes things like sleep duration, sleep latency, and subjective features of sleep. A person's capacity to maintain sleep conditions to achieve the appropriate REM and NREM sleep phases. The aim of this research is to determine the impact of gamelan music therapy. The research used a pre-experiment method with a one group pretest-posttest design. There is an influence of gamelan music therapy on sleep quality in the elderly in Banteran Village, Sumbang District, according to the sampling strategy, namely consecutive sampling, which shows a t-test analysis with a p-value of 0.001 (p 0.05).